Politik Protes Gender di Ruang Publik Yaman Pada Masa Pemerintahan Mansour Hadi - Anisa Isdiyanti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The role of women in Yamen marginalized in the political space, economic, and social. Yemen Women to be helpless due to religious authority and repressive social structures. Women tend to accept the injustice in his position as part of the community. The integration of feminist theory and the political theory of protest in public space work theory form a radical feminism that is used as a political analysis of gender inequalities in the global economy Yemen. The tendency of women to the option-radical fundamentalist ideology can be caused by poverty and lack of financial factors. This article aims to track how the politics of gender protest in the Yemeni public sphere during the 2012 Mansur Hadi administration until now. The results obtained from the search in this study, namely the influence of patriarchal culture on formal institutions; The authoritarian regime’s attitude towards gender equality; gender policy design in terms of redistribution of social power, and political decision-making and women’s movements.